Reconceptualizing the language motivation of Timorese ELLs in the Philippines - Quinto, Edward Jay Mansarate; Castillo, John Christopher Dimasaka (Penerbit Universiti Kebangsaan Malaysia, 2016)
Second language (henceforth L2) motivation has been traditionally studied from the lens of integrative motivation. However, this framework presents problems in that it is limiting and lacks insights from emerging cognitive motivational research. This paper investigated the L2 motivation of Timorese English language learners (henceforth ELLs) using Dörnyei’s (2009) L2 Motivational Self System and Markus and Nurius’s (1986) possible-selves theory. Ten Timorese ELLs studying in a school of higher learning in the Philippines participated in a free writing task and a follow-up focus group discussion. These activities aimed to examine the content and functions of the students’ two most important types of possible selves: ‘ideal L2 self’ and ‘ought-to L2 self.’ The results revealed that the students’ ‘ideal L2 self’ coincides with the original theoretical construct, which includes a promotion-focused function for studying English, i.e., to achieve personal goals and to communicate with other people. Interestingly, however, the present study corroborated Chen’s (2012) findings in the Taiwanese context that the ‘ought-to L2 self’ is not simply prevention-focused, but a mixture of prevention- and promotion-focused functions of learning English. The findings pointed to necessary research, curriculum design and pedagogical implications, which are discussed as this paper closes.